Synthetic bioactive olivetol-related amides: The influence of the phenolic group in cannabinoid receptor activity. Issue 11 (1st June 2020) - Brizzi, Antonella; Aiello, Francesca; Boccella, Serena; Cascio, Maria Grazia; De Petrocellis, Luciano; Frosini, Maria; Gado, Francesca; Ligresti, Alessia; Luongo, Livio; Marini, Pietro; Mugnaini, Claudia; Pessina, Federica; et al.
Graphical abstract: Highlights: Endocannabinoid system is a complex and dynamic pharmacological target. Cannabinoid receptor interaction and selectivity. The alkylresorcinol skeleton is a suitable scaffold for cannabinoid receptor ligands. Alkylresorcinols endowed with antinociceptive activity in vivo. Dual TRPV1/cannabinoid ligands. Abstract: Focusing on the importance of the free phenolic hydroxyl moiety, a family of 23 alkylresorcinol-based compounds were developed and evaluated for their cannabinoid receptor binding properties. The non-symmetrical hexylresorcinol derivative 29 turned out to be a CB2-selective competitive antagonist/inverse agonist endowed with good potency. Both the olivetol- and 5-(2-methyloctan-2-yl)resorcinol-based derivatives 23 and 24 exhibited a significant antinociceptive activity. Interestingly, compound 24 proved to be able to activate both cannabinoid and TRPV1 receptors. Even if cannabinoid receptor subtype selectivity remained a goal only partially achieved, results confirm the validity of the alkylresorcinol nucleus as skeleton for the identification of potent cannabinoid receptor modulators.